2021
DOI: 10.3389/fmolb.2021.636077
|View full text |Cite
|
Sign up to set email alerts
|

Models and Processes to Extract Drug-like Molecules From Natural Language Text

Abstract: Researchers worldwide are seeking to repurpose existing drugs or discover new drugs to counter the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A promising source of candidates for such studies is molecules that have been reported in the scientific literature to be drug-like in the context of viral research. However, this literature is too large for human review and features unusual vocabularies for which existing named entity recognition (NER) models are ineffective. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Therefore, an in-depth study of the key regulatory genes and drug discovery of signaling pathways is of great significance for the diagnosis and treatment of canine pyometra. Meanwhile, bioinformatics, as an emerging discipline, is used to deal with medical data to identify novel diagnosis markers and discover new drugs [12][13][14]. However, to date, no researchers have adopted this method to study the drug discovery of canine pyometra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an in-depth study of the key regulatory genes and drug discovery of signaling pathways is of great significance for the diagnosis and treatment of canine pyometra. Meanwhile, bioinformatics, as an emerging discipline, is used to deal with medical data to identify novel diagnosis markers and discover new drugs [12][13][14]. However, to date, no researchers have adopted this method to study the drug discovery of canine pyometra.…”
Section: Discussionmentioning
confidence: 99%
“…As a variety of research methods for bioinformatics, text mining and microarray data analysis have been applied to the screening of disease biomarkers, the identification of signaling pathways, and the discovery of new drugs [12][13][14][15][16]. At the same time, researchers have found a series of pathogenesis of canine pyometra by doing experiments [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The trained SpaCy and Keras models and the results of applying the models to the 198 875 articles in the CORD-19 corpus are also available in this GitHub repo. Additionally, the pretrained SpaCy model is provided as a cloud service via DLHub [13,18]. (The Keras model could not be hosted there due to compatibility issues with DLHub.)…”
Section: Data Availability and Formatsmentioning
confidence: 99%
“…The models used in this work and the datasets generated for this study can be found on GitHub at https://github.com/globus-labs/covid-nlp/tree/master/drug-ner. The models are also available on DLHub [18].…”
Section: Data and Code Availabilitymentioning
confidence: 99%